1981
DOI: 10.1259/0007-1285-54-637-12
|View full text |Cite
|
Sign up to set email alerts
|

Aging and simple cysts of the kidney

Abstract: Abdominal CT scans of 103 patients without evidence of renal disease were examined. Unsuspected simple renal cysts were demonstrated in 25 (24%). No cysts were demonstrated in patients less than 40 years old. Thereafter the number of cysts and the number of patients with cysts tended to increase with age. Cyst dimensions also increased. These observations suggest that the development of simple cysts of the kidney is related to aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
6
6

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(94 citation statements)
references
References 6 publications
10
72
6
6
Order By: Relevance
“…Simple renal cysts are benign masses and are mostly detected with ultrasonography or CT (1). Although the etiology of renal cysts is not known exactly, it is claimed that it may be caused by the obstruction and ischemia of distal convoluted tubule (13).…”
Section: Discussionmentioning
confidence: 99%
“…Simple renal cysts are benign masses and are mostly detected with ultrasonography or CT (1). Although the etiology of renal cysts is not known exactly, it is claimed that it may be caused by the obstruction and ischemia of distal convoluted tubule (13).…”
Section: Discussionmentioning
confidence: 99%
“…False-positive diagnoses of ADPKD occur with CT because of the high prevalence of simple cysts in the general population (24%-47%) (15). The reported prevalence rates of simple cysts increase with age and in men (9%, 27%, 48%, and 60% of individuals,40, 40-60, 60-80, and .80 years of age, respectively) (15)(16)(17).…”
Section: Ctmentioning
confidence: 99%
“…The reported prevalence rates of simple cysts increase with age and in men (9%, 27%, 48%, and 60% of individuals,40, 40-60, 60-80, and .80 years of age, respectively) (15)(16)(17). Bilateral simple cysts occur in 18%, 30%, and 45% of individuals,60, between 60 and 80, and .80 years of age (17).…”
Section: Ctmentioning
confidence: 99%
“…Renal cysts are acquired lesions that most commonly affect the elderly population [1] . Autopsy studies have reported a 50% incidence of renal cysts after the age of 50 years [2] .…”
Section: Introductionmentioning
confidence: 99%